(untitled) (Research Journal, 2025)
Cultural diversity in classrooms has become increasingly significant in shaping students’ learning experiences, particularly in multicultural settings like Nepal. Understanding its impact on participation, collaboration, and academic outcomes is essential for fostering inclusive education. This study examines secondary students’ perspectives on cultural diversity in classroom learning, focusing on its influence on engagement, collaborative motivation, and academic performance. Using a quantitative approach, data were collected through Likert-scale questionnaires administered to 36 grade 11-12 students from three diverse schools in Ilam district. Participants were selected through random sampling, ensuring representation across gender and ethnic groups. Findings indicate that 64% of respondents agreed diversity enhances classroom discussions, while 69% reported greater motivation for cross-cultural collaboration. However, 56% noted unequal participation opportunities, pointing to inclusivity challenges. Key results show 78% attributed improved learning outcomes to inclusive teaching methods, and 72% perceived diversity as enriching their education. Additionally, 58% endorsed diversity’s role in fostering critical thinking, and 61% supported its contribution to richer discussions. While cultural diversity enhances learning experiences and collaboration, systemic barriers such as linguistic differences and social fragmentation continue.